SYSTEM SALES PROMOTION GIRL SALARY ADMINISTRATION ON CV. PANELI - Dedy Rachmat Widodo; Cut Asiana Gemawaty, SKom, MM Cut Asiana Gemawaty, SKom, MM (Jurnal Sistem Informasi, 2001)
CV. PANELI which has a payroll administration system which has counted SPG andhas been determined with a basic salary and money crafting each SPG, overtime payand meal allowance per day each SPG. The calculations are, the meal allowance iscalculated from the number of incoming SPG employment multiplied by the amountof money that has been determined each day, as well as overtime pay that has beendetermined. Calculation of turnover of goods and bonuses are calculated from thetotal turnover per month multiplied by the specified percentage divided by twopeople. It calculations by using a computer in order to make the payroll and reports afast, accurate and precise. And besides it is useful to improve performance in dataprocessing personnel and the information quickly, precisely and accurate so that itcan assist in the CV. PANELI.